Determinanty kształtu nowej definicji budowli w podatku od nieruchomości - Paweł Borszowski (Wrocławsko-Lwowskie Zeszyty Prawnicze)
The article analyses the issue of creating a new definition of a building in the real estate tax regulation. First, the normative shape of the current definition is presented. Subsequently, the focus is put on formulating the determinants of introducing a new definition of a legal structure in the real estate tax. These determinants were established on the basis of the Regulation on the “Principles of Legislative Technique.” Hence, it serves as a determinant of the departure from the meaning of the definition contained in the Construction Law, as well as the normative novelty. Their wording made it possible to show the illustration of the legislative variant of the new tax definition of a structure, indicating the structural elements as well as definitional features.